“A DEVOURER THERI OWN KIND”. VIOLENCE, JUSTICE AND POPULAR CULTURE IN SANTA ROSA DE LOS ANDES: THE FORMS OF AUTHORITY TO EYES OD LABORER THE JOB KILLER, CHILE 1805 - Moreno Bazaes, Daniel (Revista de Historia Social y de las Mentalidades, 2016)
Through the micro-historical analysis of judicial proceedings by the authorities of the village of Santa Rosa de Los Andes and intervened by the Royal Audience of Santiago against Juan Francisco Varas, of Hacienda de Llay-Llay, responsible for at least six murders and many others crimes that undermined the local order and civil government, is intended to realize the intrinsic social organization in the Aconcagua Valley at end of the XVIII century and during the early XIX century. So that through the observation of the tensions generated by the indiscriminate use of violence, disrespect and disobedience to authority, is intended to show one of the most violent faces presented the processes of ‘campesinización’ in Chile during the colonial period, investigating the forms in which the contemporaries, administration and local authorities reacted to these practices considered unacceptable and excessive. Course it intends to account for the mechanisms deployed to control that kind of behavior and from there to deepen the horizons who adopted it and authority against a popular culture that was set apart from the "civility"